Recent review on synthesis, evaluation, and SWOT analysis of nanostructured cellulose in construction applications. (1st April 2022) - Nasir, Muhammad; Aziz, Muhammad Arif; Zubair, Mukarram; Manzar, Mohammad Saood; Ashraf, Noman; Mu'azu, Nuhu Dalhat; Al-Harthi, Mamdouh A.
Abstract: In recent years, nanotechnology has become an essential means of producing sustainable and engineered materials, resulting in high value-added products in the construction industry. Nanostructured cellulose (NSC) is a next-generation sustainable and eco-friendly material due to its favorable physicochemical characteristics for various construction industry applications. The incorporation of NSC as a green reinforcement material in concrete has exhibited promising technical, environmental, and economic merits. The presence of NSC in concrete structures has shown significant improvement in mechanical strength, durability, and microstructure properties. In this present review, a brief overview of the different NSC synthesis processes, as well as their yield and physicochemical characteristics is presented. The review critically evaluates the performance of NSC in concrete applications as a cementitious material and fiber additive to understand and demonstrate the reaction kinetics, rheology, mechanical properties, durability, and microstructural characteristics. The reaction mechanisms involved in enhancing the properties of NSC-engineered cementitious composites are also compiled from the literature. The shortcomings in the synthesis and evaluation of the developed binders are highlighted. Strengths, weaknesses, opportunities, and threats (SWOT) analysis was used to evaluate NSC in construction applications for insight into the relevance of its adoption and the interpretation of an existing or planned NSC business model. Moreover, potential recommendations have been drawn to bridge the knowledge gap between what is known and the future use of NSC in civil engineering applications. Graphical abstract: Image 1 Highlights: Overview of the synthesis processes and characterization of nanostructured cellulose (NSC) is presented. Critical evaluation of macro- and micro-level properties of NSC-based construction products. NSC of (0.1–2 wt%) in concrete showed 30–50% improvement in flexural strength. SWOT analysis of NSC-based concrete is performed. NSC for construction industry is step toward circular economy and reducing carbon foot print.